Bioinspired Fabrication of Insensitive HMX Particles with Polydopamine Coating. Issue 6 (28th July 2016) - Zhu, Qing; Xiao, Chun; Li, Shangbin; Luo, Guan
Abstract: The development of a facile method for large scale production of insensitive HMX particles is of great importance for energetic materials, especially for insensitive munitions. Inspired by mussels, HMX particles with a thin, robust, wettable and uniform coating based on the self‐polymerization of dopamine were prepared by one‐step solution stirring processes in the study. The as‐prepared HMX@PDA particles showed stable shape, size, and polymorphy compared with original HMX particles. With PDA (polydopamine) coating, the HMX@PDA particles exhibited better wettability, which could improve the adhesive properties between particles and other liquid components in a PBX (plastic bonded explosive). Furthermore, the mechanical sensitivities were decreased for the HMX@PDA particles because of the uniform and smooth PDA coating decreasing the hot spots on the surface of the HMX particles. HMX@PDA particles produced by a facile scalable process might provide a promising substitute for sensitive HMX particles to enhance the safety and adhesive properties when used in PBX. Abstract :